Kant on Free Will and Theoretical Rationality (2018)
The focus of this essay is Kant’s argument in the Groundwork for the Metaphysics of Morals (GMS) III that regarding oneself as rational implies regarding oneself as free. After setting out  an interpretation of how the argument is meant to go (§§1-2), I argue that Kant fails to show that regarding oneself as free is incompatible with accepting universal causal determinism (§3). However, I argue that the argument succeeds in showing that regarding oneself as rational is inconsistent with accepting universal causal determinism if one accepts a certain, plausible view of the explanation of events (§4).